Key concepts in operations management - Leseure, Michel; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2010)
'Key Concepts in Operations Management' introduces a selection of key concepts and techniques in the field. Concise informative and contemporary, with consideration given to explaining the principles of the topic, as well as the relevant debates and literature, the book contains over 50 concept entries including.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Production management; Electronic books